2001
DOI: 10.1002/jpp.391
|View full text |Cite
|
Sign up to set email alerts
|

Position isomer separation of non-peripheral substituted zinc dibenzo-di(3,4-pyrido)porphyrazines

Abstract: ABSTRACT:The cyclotetramerisation products from the 1, 8-diazabicyclo[5,4,0]undec-7-ene catalysed reaction of a 1:1 mol mixture of 3,6-didecylphthalonitrile and 3,4-dicynopyridine in the presence of zinc chloride have been isolated by chromatography. The fractions comprise zinc octadecylphthalocyanine and compounds in which one, two, three and four pyridinoid rings replace the didecylbenzenoid moiety. The zinc bis(1,4-didecylbenzo)bis(3,4-pyrido)porphyrazine fraction was separated further into four sub-fractio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 36 publications
2
35
1
Order By: Relevance
“…Most of this type of phthalocyanine compounds have originated from Cook's group, 53 which developed a very elegant way for preparation of the key precursors, e.g. 3,6-dialkylphthalonitriles, using the Diels-Alder reaction (Scheme 7).…”
Section: Methodsmentioning
confidence: 99%
“…Most of this type of phthalocyanine compounds have originated from Cook's group, 53 which developed a very elegant way for preparation of the key precursors, e.g. 3,6-dialkylphthalonitriles, using the Diels-Alder reaction (Scheme 7).…”
Section: Methodsmentioning
confidence: 99%
“…These results mean that the 5 and 6 have a proposed structure in accordance with the stoichiometric ratio. Of course, each compound is a mixture of five regioisomers which possess two pyridine rings and two non-peripheral substituted benzenoid rings at different locations in the molecules as previously reported [11]. In Scheme 1, typical molecular structures of 5 and 6 are described.…”
Section: Synthesismentioning
confidence: 82%
“…Undoubtedly, the obtained phthalocyanines and their related compounds were composed of only one constituent, while on the other hand, it is thought that target compounds zinc bis(didecylthiobenzo)-bis(pyrido)porphyrazines 5 and 6, synthesized from mixed raw materials by cross cyclotetramerization, were prepared as a mixture of products which have different number of pyridine rings in the molecule. The authors previously reported that alkylbenzopyridoporphyrazine synthesized from mixed raw materials has desired molecular structure for its main constituents [11].…”
Section: Synthesismentioning
confidence: 99%
See 2 more Smart Citations